2004
DOI: 10.1051/0004-6361:20041334
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CCD astrolabe multi-site solar diameter observations

Abstract: Abstract.Results are presented of measured variations of the photospheric solar diameter, as concurrently observed at three sites of the R2S3 (Réseau de Suivi au Sol du Rayon Solaire) consortium in 2001. Important solar flux variations appeared in that year, just after the maximum of solar activity cycle 23, make that time stretch particularly promising for a comparison of the multi-site results. The sites are those in Turkey, France and Brasil. All observations are made with similar CCD solar astrolabes, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
(13 reference statements)
1
12
0
1
Order By: Relevance
“…On long-term trend of the radius variation with 11-year, however, contradictory results are present about amplitudes and phases (Delache, Laclare & Sadsoud 1985;Ulrich & Bertello 1995;Laclare et al 1996;Pap et al 2001;Andrei et al 2004;Noël 2004). Besides, some authors (Wittmann 1997(Wittmann , 2003Brown & Christensen-Dalsgaard 1998;Kuhn et al 2004) have put forward that there is no significant variation in the observed diameter.…”
Section: Introductionmentioning
confidence: 99%
“…On long-term trend of the radius variation with 11-year, however, contradictory results are present about amplitudes and phases (Delache, Laclare & Sadsoud 1985;Ulrich & Bertello 1995;Laclare et al 1996;Pap et al 2001;Andrei et al 2004;Noël 2004). Besides, some authors (Wittmann 1997(Wittmann , 2003Brown & Christensen-Dalsgaard 1998;Kuhn et al 2004) have put forward that there is no significant variation in the observed diameter.…”
Section: Introductionmentioning
confidence: 99%
“…So, we have used a method to correct the radius measurements recorded by the solar astrolabes with CCD video camera. In our case, the best way is improved by Sinceac (1998), Sinceac et al (1998), Chollet and Sinceac (1999) and it gives quite homogenous results as shown in several papers published by Golbasi et al (2001), Reis Neto et al (2003, Andrei et al (2004), Kiliç et al (2005), Kiliç and Golbasi (2009). As a result, the astrolabe measurements can be made homogenous by the applied method for the seeing effect.…”
Section: Resultsmentioning
confidence: 68%
“…It has been reported by several authors that the solar radius displays the temporal variations from a few days to several years (Eddy and Boornazian 1979;Gilliland 1981;Delache et al 1985Delache et al , 1993Ulrich and Bertello 1995;Laclare et al 1996;Pap et al 2001;Moussaoui et al 2001;Reis Neto et al 2003;Andrei et al 2004;Noël 2004;Egidi et al 2006;Djafer et al 2008b;Kiliç andGolbasi 2009, 2011). Such variations are an important topic for our understanding of the static and dynamic structure of the solar interior and the solar atmosphere, if any.…”
Section: Introductionmentioning
confidence: 95%
“…One of these widely used instruments is the solar astrolabe. The description of the visual and CCD generation of this instrument and the results obtained for the diameter of the Sun are given by Laclare et al (1991Laclare et al ( , 1996Laclare et al ( , 1999, Delmas et al (2006), Andrei et al (2004), Gölbaşi et al (2000Gölbaşi et al ( , 2001, Jilinski et al (1999), Penna et al (2002), and Kilic et al (2005).…”
Section: Introductionmentioning
confidence: 99%